Deaths by suicide and their relationship with general and psychiatric hospital discharge: 30-year record linkage study. (April 2014) - Dougall, Nadine; Lambert, Paul; Maxwell, Margaret; Dawson, Alison; Sinnott, Richard; McCafferty, Susan; Morris, Carole; Clark, David; Springbett, Anthea
Abstract : Background: Studies have rarely explored suicides completed following discharge from both general and psychiatric hospital settings. Such research might identify additional opportunities for intervention. Aims: To identify and summarise Scottish psychiatric and general hospital records for individuals who have died by suicide. Method: A linked data study of deaths by suicide, aged ⩾15 years from 1981 to 2010. Results: This study reports on a UK data-set of individuals who died by suicide ( n = 16 411), of whom 66% ( n = 10 907) had linkable previous hospital records. Those who died by suicide were 3.1 times more frequently last discharged from general than from psychiatric hospitals; 24% of deaths occurred within 3 months of hospital discharge (58% of these from a general hospital). Only 14% of those discharged from a general hospital had a recorded psychiatric diagnosis at last visit; an additional 19% were found to have a previous lifetime psychiatric diagnosis. Median time between last discharge and death was fourfold greater in those without a psychiatric history. Diagnoses also revealed that less than half of those last discharged from general hospital had had a main diagnosis of 'injury or poisoning'. Conclusions: Suicide prevention activity, including a better psychiatric evaluation of patients within general hospital settings deserves more attention. Improved information flow between secondary and primary care could be facilitated by exploiting electronic records of previous psychiatric diagnoses.